2017
DOI: 10.1152/japplphysiol.00505.2017
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning does not prevent acute mountain sickness after rapid ascent to 3,450 m

Abstract: = 0.496 for LLS; = 0.320 for AMS-C score) of AMS. RIPC also had no significant effect on SPAP [maximum after 10 h at high altitude; RIPC: 33 (SD 8) mmHg; controls: 37 (SD 7) mmHg; = 0.19]. This study indicates that RIPC, performed immediately before passive ascent to 3,450 m, does not attenuate AMS and the magnitude of high-altitude pulmonary hypertension. Remote ischemic preconditioning (RIPC) has been reported to improve neurologic and pulmonary outcome following an acute ischemic or hypoxic insult, yet the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…Nocturnal expiratory positive airway pressure (EPAP) administered via a single-use nasal strip during sleep is not effective for AMS prophylaxis, 67 nor is a regimen of remote ischemic preconditioning. 68 No studies have examined short-term oxygen use in the form of either visits to oxygen bars or over-the-counter oxygen delivery systems by which individuals inhale oxygenenriched gas from a small prefilled canister. Due to the small volume of gas (2 to 10 L/canister) and short duration of administration, these interventions are unlikely to be of benefit and, as a result, have no role in AMS/HACE prevention.…”
Section: Other Optionsmentioning
confidence: 99%
“…Nocturnal expiratory positive airway pressure (EPAP) administered via a single-use nasal strip during sleep is not effective for AMS prophylaxis, 67 nor is a regimen of remote ischemic preconditioning. 68 No studies have examined short-term oxygen use in the form of either visits to oxygen bars or over-the-counter oxygen delivery systems by which individuals inhale oxygenenriched gas from a small prefilled canister. Due to the small volume of gas (2 to 10 L/canister) and short duration of administration, these interventions are unlikely to be of benefit and, as a result, have no role in AMS/HACE prevention.…”
Section: Other Optionsmentioning
confidence: 99%
“…In this study, SO 2 was approximately 8% lower in AMS ( p < 0.001), while sPAP was only 3 mmHg higher in AMS than in healthy individuals ( p = 0.117). In a study performed at 3450 m in the Jungfraujoch Research Station on a possible protective effect of remote ischemic preconditioning [58], there was no significant difference in SO 2 (0.386) and in sPAP ( p = 0.934) between healthy subjects and those with AMS from the placebo group on the first morning after ascent. While on day three at high-altitude the difference in SO 2 between controls and AMS was increased slightly (+3%; p = 0.041), there was no difference in sPAP between both groups.…”
Section: Acute Mountain Sickness (Ams)mentioning
confidence: 99%
“…Relation between sPAP and SO 2 in acute mountain sickness (AMS) and in healthy controls. Individual values from the placebo-group of a study on effects of ischemic preconditioning performed at 3450 m at the Jungfraujoch Research Station [58] and from the placebo group of a study on effects of inhaled budesonide at the Capanna Margherita (4559 m) [41]. Data split by AMS have not been reported in these publications.…”
Section: Figurementioning
confidence: 99%
“…One article found that IPC did not have an effect on the presence and severity of acute mountain sickness in altitude. This article also found that IPC had no effect on hypoxic pulmonary vasoconstriction in high altitude 58 …”
Section: Resultsmentioning
confidence: 65%
“…Recently, the results have evolved to highlight the innovative effects of IPC on exercise performance. Indeed, altitude performance has been evaluated,56, 57, 58 along with the effects of IPC on exercise recovery,33, 34 , 43, 51 , 61, 62 , 66 fatigue,30, 32 , 69 and rating of perceived exertion 30 . However, research has been reexamined as a result of a lack of evidence to explain the mechanisms responsible for the outcome of IPC 75 .…”
Section: Discussionmentioning
confidence: 99%